“Taiga Boulevards”: the Park Improvement Concept for Sayansk - Kazakova, Valentina (project baikal, 2019)
The peculiarities and the opportunities of the development of a small town are presented. The idea of preservation of greenery is used in the park improvement concept. The design process consists of several stages and includes a complex analysis of the site and the town, working with inhabitants and investors, as well as formulation of the concept basing on the revealed identity, the citizens’ needs and the capacity of the territory.
Keywords: nature; Sayansk; public space; participation of inhabitants; improvement; park; development of urban territories